PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VISUAL BASIC APPLICATION POWERPOINT PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Rosmayanti, Dea; Zanthy, Luvy Sylviana (IKIP Siliwangi, 2019)
This research is development research. This study aims to develop VBA Powerpoint based learning media on SPLDV material for class VIII junior high school students. Samples for this research are taken from one of junior high school in Bandung. This study refers to the ADDIE development model which includes five stages, namely: Analysis (Analysis Phase), Design (Design Phase), Development (Development Phase), Implementation (Implementation Phase), and Evaluation (Evaluation Phase). The instrument of this research is in the form of assessment sheets for material experts, media experts, teachers and students. Based on the analysis of learning media through the instruments given to material experts, media experts, teacher and students obtained the following results, material experts stated that the product was very valid with an average value of 3.64 and media experts stated that the product was valid with an average value of 3.06. While the results of teacher responses can be concluded that the product is very valid with an average value of 3.50 and from the results of student responses can be concluded that the product is valid with an average value of 3.18.1